Observational constraints on glyoxal production from isoprene oxidation and its contribution to organic aerosol over the Southeast United States. Issue 16 (23rd August 2016) - Li, Jingyi; Mao, Jingqiu; Min, Kyung‐Eun; Washenfelder, Rebecca A.; Brown, Steven S.; Kaiser, Jennifer; Keutsch, Frank N.; Volkamer, Rainer; Wolfe, Glenn M.; Hanisco, Thomas F.; Pollack, Ilana B.; Ryerson, Thomas B.; et al.
Abstract: We use a 0‐D photochemical box model and a 3‐D global chemistry‐climate model, combined with observations from the NOAA Southeast Nexus (SENEX) aircraft campaign, to understand the sources and sinks of glyoxal over the Southeast United States. Box model simulations suggest a large difference in glyoxal production among three isoprene oxidation mechanisms (AM3ST, AM3B, and Master Chemical Mechanism (MCM) v3.3.1). These mechanisms are then implemented into a 3‐D global chemistry‐climate model. Comparison with field observations shows that the average vertical profile of glyoxal is best reproduced by AM3ST with an effective reactive uptake coefficient γ glyx of 2 × 10 −3 and AM3B without heterogeneous loss of glyoxal. The two mechanisms lead to 0–0.8 µg m −3 secondary organic aerosol (SOA) from glyoxal in the boundary layer of the Southeast U.S. in summer. We consider this to be the lower limit for the contribution of glyoxal to SOA, as other sources of glyoxal other than isoprene are not included in our model. In addition, we find that AM3B shows better agreement on both formaldehyde and the correlation between glyoxal and formaldehyde ( R GF = [GLYX]/[HCHO]), resulting from the suppression of δ‐isoprene peroxy radicals. We also find that MCM v3.3.1 may underestimate glyoxal production from isoprene oxidation, in part due to an underestimated yield from the reaction of isoprene epoxydiol (IEPOX) peroxy radicals with HO2 . Our work highlights that the gas‐phase production of glyoxal represents a large uncertainty in quantifying its contribution to SOA. Key Points: Box model‐simulated glyoxal production from three isoprene oxidation mechanisms differ greatly Aerosol uptake of glyoxal was constrained using airborne in situ measurements and a global model Model results show that glyoxal contributes 0–14% of SOA in the Southeast U.S. during summer